High Piezoelectric Longitudinal Coefficients in Sol–gel PZT Thin Film Multilayers. Issue 7 (17th March 2014) - Balma, Davide; Mazzalai, Andrea; Chidambaram, Nachiappan; Sandu, Cosmin S.; Neels, Antonia; Dommann, Alex; Hess, Peter; Binz, Dieter; Muralt, Paul; Brennecka, G.
<x xml:space="preserve">Abstract</x> A five‐layer stack of lead zirconate titanate (PZT) thin films with Pt electrodes was fabricated for potential applications in nanoactuator systems. The 1 μm thick PZT films were deposited by a sol–gel technique, the platinum electrodes by sputtering. The PZT films were crack‐free, in spite of the use of silicon as a substrate, suggesting an increased toughness of the metal–ceramic composite. For piezoelectric characterization, the intermediate electrodes were liberated by successive etching of the PZT and Pt layers, obtaining a functional three‐ layer stack. A total thickness change of 5.2 nm was achieved with 10 V, measured by double beam laser interferometry. The small signal response was obtained as 0.49 nm/V. Finite element simulations were made to account for the thickness change in the substrate due to the transverse piezoelectric effect. The average response corresponds to an average d33, f of 120 pm/V. The multiple annealed buried layers show clearly a better performance with up to 175 pm/V. It is concluded that the electrode interfaces in the interior exhibit higher qualities, as supported by transmission electron microscopy, and that the multiple anneals were beneficial for PZT thin film quality.